Junior High School Teachers and Students’ Attitude toward Teaching and Learning Mathematics through Problem Solving: A Case Study from Mampong Municipality - Twumasi, Ebenezer Birch; Afful, JoyceAsante (American Journal of Education and Practice, 2022)
Purpose: Effectiveness of education depends on factors which include teachers' instructional role associated with students' learning outcomes. Teachers' attitude is an enduring system of their beliefs, feelings and actions which invariably influence students' achievement in mathematics learning. This study sought to investigate into Junior High School (JHS) mathematics teachers and students' attitudes toward teaching and learning mathematics through problem-solving instructional strategy. Methodology: A cross - sectional exploratory survey design was employed to obtain a snapshot of what pertained in the classrooms of the selected Junior High Schools. Questionnaires for measuring teachers and students' attitude were pilot tested to ensure scale reliability. Descriptive and inferential statistics were used for the data analysis. Spearman' rank correlation was calculated to establish the nature of relationship between teachers and students' attitude, at a fixed significance level of 0.05. Findings: It was revealed that there existed positive but weak relationship between teachers and students' attitudes toward teaching and learning mathematics through problem solving. Findings from this study were not quite different from the studies reviewed in the literature that showed that teachers' attitude influence their choice of teaching strategy and the quality of teaching students receive. Format for conducting external examination, time available for teaching topics in the syllabus, and students' entry behaviour were found to be determining factors for teachers' choice of instructional strategy. It can be inferred that though students considered problem solving instructional approach as challenging, but they do not despise its use in mathematics learning. Recommendations: From this study, subject-based workshops or professional development sessions must be organized by District Education Office at the beginning of every term for the JHS mathematics teachers. Students must equally be encouraged by teachers through specific assignments that involve the use of problem-solving strategies. workshops, District Education Office should provide mathematics teachers with materials that will enable them to model mathematical concepts in classroom.